Influence of Air Temperature on Physical Characteristics and Bioactive Compounds in Vacuum Drying of Arthrospira Spirulina. Issue 2 (6th March 2016) - Larrosa, A.P.Q.; Comitre, A.A.; Vaz, L.B.; Pinto, L.A.A.
Abstract: The aim of this study was to evaluate the effects of different temperatures in vacuum drying of Arthrospira Spirulina sp. on the physical properties and on the bioactive compounds, and to compare with the traditional oven dryer. The samples were evaluated according to phycocyanin content, phenolic compounds, lipid oxidation, color parameters and rehydration. The phenolic methanol extracts were analyzed by FTIR, and thermal analysis (DSC), scanning electronic microscopy and X‐ray diffraction of the samples were also performed. The results showed that the characteristics of the dried products were influenced by the different temperatures of the drying methods. Vacuum drying at 40C was the more suitable to dry Arthrospira Spirulina sp. in relation to the characteristics products due to the minor losses of phycocyanin content, the great source of phenolic compounds, the minor lipid oxidation, the good rehydration capacity and the highest thermal stability. Pratical Applications: Arthrospira Spirulina sp. is a microalgae which is a promising source of compounds with biological activity that could be used as functional ingredients, due to presence of pigments, phenolic compounds and fatty acids. However, this algae is very perishable and it should be dried after cultivation in order to prevent fungal deterioration. Phycocyanin content, phenolic compounds and lipid oxidation of the Arthrospira Spirulina sp. are affected by temperature and time drying processing. Thus, the vacuum drying process is a technique which leads to a product with best quality due to the low air temperatures and less oxygen content present in environment of dryer under subatmospheric pressure. Therefore, selection of the most appropriate technique and the drying conditions are very important to avoid major losses of bioactive compounds during the drying process of Arthrospira Spirulina sp.